Nessuna isola è un'isola - Giorgio, Costa (Scuole di dottorato, 2008)
This book, the result of research carried out for the PhD in landscape design at the Florence University Faculty of Architecture, elaborates a methodological process for landscape planning in the smaller islands, comparing a number of case studies identified in the western Mediterranean, and illustrating many individual cases that broaden the overview of the specific demands of the islands. The research evolves at both scientific and humanistic levels, setting up a virtual parallel between the methods of construction of the cinema narration (which has frequently focused on the island in its various meanings) and the construction process of tools for territorial and landscape planning. The objective is to define a method that can monitor the sustainable development of the smaller islands, guiding it towards an enhanced awareness of their resources and potential, mindful of the threat of definitive loss in the case of mistaken decisions.